Zofia Moraczewska (1873-1958). Kobieta-polityk II Rzeczypospolitej - Florczak, Ilona (Acta Universitatis Lodziensis. Folia Historica, 2003)
The general aim of this article is to present Zofia Moraczewska (1873-1958) as a socialist, fighter for Polish independence, a leader of many Polish feminine movements in Austrian sector of partitioned Poland and in the Second Republic and as member of a Parliament in 1919-1922, 1928-1930 and 1930-1935. From 1896 she was member of Polish Social-Democratic Party of Galicia and Silesia (Polska Partia Galicji i Śląska – PPSD) in which she concentrated on equality of women and workers’ rights. During the First World War Zofia Moraczewska as the President of League of Women Galicia and Silesia (Liga Kobiet Galicji i Śląska), which was connected with Leading National Committee (Naczelny Komitet Narodowy), stood up for Polish rights to independence. She, like her husband Jędrzej Moraczewski, was a follower of Józef Piłsudski group composed of activists, aiming for regaining of the indcpedence of Poland. After regaining the independence, Zofia Moraczewska was elected, in 1919, to Legislative Sejm as the only one female representative of the socialist movement. She was the first woman who spoke in Polish parliament. As a parliamentarian she continued fighting for equality of women and workers rights. After dissolving the Parliament in 1922 she resigned from political activity for the next four years. After coup d ’etat of May she joined new politic group supported J. Piłsudski’ s governments. She became the president of new pro-government women organisation Women’ Civil Work Union (Związek Pracy Obywatelskiej Kobiet - ZPOK). In 1928 and 1930 she was elected to the Parliament from the list of Non-party Block of Co-operation with the Government (Bezpartyjny Blok Współpracy z Rządem – BBWR). During the cadences of 1928-1930 and 1930-1935 she was a member of parliamentarian club of BBWR and she usually supported political ideas of the club. In 1932 and 1933 after passing ‘the uniting laws’ there arose a conflict between Z. Moraczewska and the President of BBWR Walery Sławek. As a result of the conflict Z. Moraczewska had to resign from the position of the president of ZPOK. In 1935 she and her followers left the Union and created new organisation the Social Mutual Aid of Women (Samopomoc Społeczna Kobiet 0 SSK). From 1935 she was staying away from mainstream political life in Poland. Until she died she was faithful to her social political ideas, which were the same as her husband’s, Jędrzej Moraczewski the first Prime Minister of the Second Republic. The most important aims of her activity were connected with equality of women and workers rights. Zofia Moraczewska died the 19 of November 1958. She left a few versions of her memoirs, which are useful sources for studying feminine movements in Poland between wars.